1997
DOI: 10.1111/j.1365-2710.1997.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of quality of life, compliance, clinical outcomes and life satisfaction: a cross-sectional study on hypertensive geriatrics

Abstract: Age showed a significant negative correlation with physical functioning (r = 0.339, P< or =0.0127) and physical role (r=0.335, P< or =0.0148). The physical role facet of SF-36 is correlated with life satisfaction in geriatrics (r = 0.316, P < or =0.0219). A regression analysis (backward stepwise) not including bodily pain (BP) and general health (GH) resulted in a model explaining 22.3% of variance (n = 54, F = 2.252, P < or = 0.0543). Physical role (P < or = 0.0084) and mental health facets (P< or = 0.0184) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…With the exception of the negative association, the current study findings agree with those in the literature [1,16,26,27]. However, Carbello et al concluded that certain HRQoL domains are closely related to medication adherence in an HIV population [28].…”
Section: Discussionsupporting
confidence: 91%
“…With the exception of the negative association, the current study findings agree with those in the literature [1,16,26,27]. However, Carbello et al concluded that certain HRQoL domains are closely related to medication adherence in an HIV population [28].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies provide inconsistent findings ranging from weak to strong correlation between the quality of life among hypertensive population and adherence to treatment [ 23 , 24 ]. The differences in the findings are probably due to the measurement of HRQoL using different instruments such as the World Health Organization Quality of Life Instrument (WHOQOL-BREF), EQ-5D-3L, Short Form 36 (SF36), or SF-12 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study among geriatric hypertensive patients, no association was demonstrated between self-reported medication adherence and HRQoL. 36 Again, another study among adults with hypertension aged 35 to 80 years showed a weak negative correlation between self-reported medication adherence and HRQoL. 37 The mechanisms through which HRQoL affects adherence remain unknown.…”
Section: Discussionmentioning
confidence: 99%